Assessment of Regional Functional Effects of Surgical Treatment in Thoracic Insufficiency Syndrome via Dynamic Magnetic Resonance Imaging. (4th January 2023) - Tong, Yubing; Udupa, Jayaram K.; McDonough, Joseph M.; Wu, Caiyun; Sun, Changjian; Xie, Lipeng; Lott, Carina; Clark, Abigail; Mayer, Oscar H.; Anari, Jason B.; Torigian, Drew A.; Cahill, Patrick J.
Abstract : Background: Quantitative regional assessment of thoracic function would enable clinicians to better understand the regional effects of therapy and the degree of deviation from normality in patients with thoracic insufficiency syndrome (TIS). The purpose of this study was to determine the regional functional effects of surgical treatment in TIS via quantitative dynamic magnetic resonance imaging (MRI) in comparison with healthy children. Methods: Volumetric parameters were derived via 129 dynamic MRI scans from 51 normal children (November 2017 to March 2019) and 39 patients with TIS (preoperatively and postoperatively, July 2009 to May 2018) for the left and right lungs, the left and right hemi-diaphragms, and the left and right hemi-chest walls during tidal breathing. Paired t testing was performed to compare the parameters from patients with TIS preoperatively and postoperatively. Mahalanobis distances between parameters of patients with TIS and age-matched normal children were assessed to evaluate the closeness of patient lung function to normality. Linear regression functions were utilized to estimate volume deviations of patients with TIS from normality, taking into account the growth of the subjects. Results: The mean Mahalanobis distances for the right hemi-diaphragm tidal volume (RDtv) were −1.32 ± 1.04 preoperatively and −0.05 ± 1.11 postoperatively (p = 0.001). Similarly, the mean Mahalanobis distances for the right lung tidal volume (RLtv) were −1.12 ± 1.04 preoperatively and −0.10 ± 1.26 postoperatively (p = 0.01). The mean Mahalanobis distances for the ratio of bilateral hemi-diaphragm tidal volume to bilateral lung tidal volume (BDtv/BLtv) were −1.68 ± 1.21 preoperatively and −0.04 ± 1.10 postoperatively (p = 0.003). Mahalanobis distances decreased after treatment, suggesting reduced deviations from normality. Regression results showed that all volumes and tidal volumes significantly increased after treatment (p < 0.001), and the tidal volume increases were significantly greater than those expected from normal growth for RDtv, RLtv, BDtv, and BLtv (p < 0.05). Conclusions: Postoperative tidal volumes of bilateral lungs and bilateral hemi-diaphragms of patients with TIS came closer to those of normal children, indicating positive treatment effects from the surgical procedure. Quantitative dynamic MRI facilitates the assessment of regional effects of a surgical procedure to treat TIS. Level of Evidence: Diagnostic Level II . See Instructions for Authors for a complete description of levels of evidence.